Hepatocellular Carcinoma With Tumor Thrombus Occupying the Right Atrium and Portal Vein. Issue 34 (August 2015) - Luo, Xin; Zhang, Binhao; Dong, Shuilin; Zhang, Bixiang; Chen, Xiaoping; Takafumi, Ichida.
<x xml:space="preserve">Abstract</x> Abstract Hepatocellular carcinoma (HCC) patients with tumor thrombus extended through the major hepatic veins and inferior vena cava into the right atrium (RA) are rare, and most cases are considered as the advanced stage with a poor prognosis. We report a case of HCC with a tumor thrombus extending into the RA and a tumor thrombus in the portal vein. A literature search for case reports was performed on PubMed. Compared with the published literature, our case is one of the youngest patients, but with the most advanced HCC that invades both the hepatic inflow and outflow vasculature. For this patient, we resected the tumor thrombus in the RA with the use of cardiopulmonary bypass, and then removed the tumor thrombus in the portal vein and ligated the left branch of portal vein. Because of insufficient remnant liver volume, microwave ablation and transcatheter arterial chemoembolization were performed to control the growth of HCC. The patient survived 6 months after surgery. This case suggests that for patients with extension of HCC into the RA and portal vein, surgery is a useful therapeutic modality, even in case that liver tumor cannot be resected.